2022
DOI: 10.3390/s22239038
|View full text |Cite
|
Sign up to set email alerts
|

Noise in ICUs: Review and Detailed Analysis of Long-Term SPL Monitoring in ICUs in Northern Spain

Abstract: Intensive care units (ICUs) are busy and noisy areas where patients and professional staff can be exposed to acoustic noise for long periods of time. In many cases, noise levels significantly exceed the levels recommended by the official health organisations. This situation can affect not only patient recovery but also professional staff, making ICUs unhealthy work and treatment environments. To introduce the measures and reduce the acoustic noise in the ICU, acoustic noise levels should first be measured and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…This study revealed elevated levels of noise in the investigated Brazilian NICU, consistent with findings from other published literature [19,[25][26][27][28][29][30][31][32][33].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This study revealed elevated levels of noise in the investigated Brazilian NICU, consistent with findings from other published literature [19,[25][26][27][28][29][30][31][32][33].…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are consistent with a study conducted in a Spanish neonatal intensive care unit (NICU), which assessed noise levels over a 20-day period. The Spanish study found that noise consistently remained high across morning, afternoon, and night shifts, with minor fluctuations between shifts [19].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation